The effect of behavioral counseling using self-management techniques on senior high school students’ self-confidence - Rachmawati, Ni Luh Sri; Dantes, I Nyoman; Gading, I Ketut; Suarni, Ni Ketut (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2026)
Self-confidence is one of the psychological aspects that has a direct effect on the academic and social development of senior high school students. Although this variable is commonly studied, research on behavioral counseling that addresses it through a structured approach is still limited, particularly research that combines gain score and effect size analyses within a quasi-experimental design. Most previous studies have focused more on motivation, learning discipline, or maladaptive behavior, so self-confidence within structured school counseling has not received sufficient attention. This study was conducted with the purpose of examining how behavioral counseling combined with self-management techniques relates to the improvement of self-confidence among tenth-grade students at a public senior high school in Denpasar, Indonesia. The approach used in this study was quantitative, with a quasi-experimental non-equivalent pretest-posttest control group design. Sixty students were selected through purposive sampling and then divided into an experimental group and a control group. The experimental group participated in six structured counseling sessions incorporating self-management techniques, while the control group only received regular school counseling services. The data were collected using a self-confidence questionnaire consisting of 30 items (Cronbach’s Alpha = 0.89). The analysis included descriptive statistics, the Shapiro-Wilk normality test, Levene’s test of homogeneity, the paired-samples t-test, and the independent-samples t-test on the gain scores. The results of the analysis showed a significant difference in gain scores between the two groups (p < 0.05), with a large effect size (Cohen’s d = 1.32). Students in the experimental group showed greater improvement in self-confidence compared with those in the control group. Regarding its novelty, this study combines behavioral counseling and self-management techniques in a structured manner within school counseling practice and also uses gain scores together with effect size to strengthen the empirical interpretation. The results suggest that counseling interventions designed systematically and based on a theoretical foundation can support the development of self-confidence in school settings with similar contexts.